Aterro zero na indústria petroquímica: proposta e avaliação de um biodigestor anaeróbio em cozinhas industriais - Antunes, Gabriel Fernandes (Universidade Federal de São Carlos, 2025)
The inadequate management of industrial solid waste represents a significant environmental and economic challenge. Therefore, this study aims to analyze the technical and economic viability, as well as the main environmental impacts, of implementing a compact anaerobic biodigester for the treatment of organic waste generated in the industrial kitchens of a company in the chemical and petrochemical sector, as an initial strategy for adopting the Zero Landfill concept. The methodology consisted of a qualitative-quantitative case study, involving waste characterization, cost analysis of the current system, comparative evaluation of technical-commercial proposals, and the qualitative identification of the proposed alternative's socio-environmental impacts. The results indicated an average generation of 277.73 kg/day of organic waste, whose current landfill management represents an annual cost exceeding BRL 100,000.00. The comparative analysis demonstrated that, while the external composting alternative proved to be economically unfeasible, the biodigestion solution (Supplier A) presented itself as advantageous, with an investment of BRL 17,000.00 and a payback period of approximately 11 months, generating savings over BRL 40,000.00 in three years. Environmentally, the proposal allows diverting 73.3 annual tons of waste from landfill, avoiding methane generation, equivalent to approximately 125 tons of CO2e per year, also identifying an estimated energy potential of 44 MWh/year, in addition to eliminating external transport emissions. It is concluded that implementing the technology is a viable and strategic alternative, as it mitigates operational costs and promotes significant environmental, social, and operational benefits, aligning the company with the principles of the Circular Economy and sustainability.
Zero waste to landfill in the petrochemical industry: proposal and evaluation of an anaerobic biodigester in industrial kitchens
Keywords: Gestão de resíduos industriais; Viabilidade econômica; Economia circular; Biodigestão anaeróbia; Aterro zero; Industrial waste management; Economic viability; Circular economy; Anaerobic digestion; Zero landfill; ENGENHARIAS::ENGENHARIA SANITARIA::SANEAMENTO BASICO; 6. Água Potável e Saneamento; 12. Consumo e Produção Responsáveis; 11. Cidades e Comunidades Sustentáveis